Analysis of MIG Welding Parameters on the Welding Quality of Apron Feeders in the BINS Workshop Unit of PT. XYZ - Aldo Alfattah Sudjono; Nadry Heroza; Randi Purnama Putra; Purwantono (Unversitas Negeri Padang, 2026)
This study examines the effect of MIG Welding parameter variations on the quality of Welded joints in apron feeder components at the BINS Workshop Unit of PT. XYZ. The issue raised is that variations in Welding practices in workshops can cause visual defects and reduce the reliability of heavy-duty components. The objectives of this study are to identify the variations in MIG parameters applied in the field, analyze the quality of Welds based on visual inspection, and determine the most suitable parameters to be adopted for Welding components as a whole. The Method used was a field experiment with a qualitative descriptive approach: Welding was performed on SS400 plate joints (10 mm–6 mm and 4 mm–6 mm) using ER70S-6 wire and CO2 shielding gas with two sets of parameters (wire feed speed 7 m/s vs. 5 m/s), and the results were analyzed through standard visual inspection. The results showed different characteristics: parameters with a higher wire feed produced deeper penetration and wider beads (more suitable for thick plates), while parameters with a lower wire feed provided process stability and a fairly good visual appearance, which was chosen for overall Welding (voltage = 20–22 V; wire feed = 5 m/min). Although the process was generally effective, visual defects such as spatter, porosity/pin hole, cold lap, stop-start, and surface concavity were detected. The study recommends parameter control, machine maintenance, and operator competency improvement to minimize defects and increase joint reliability.